Uremic Pericarditis in a Patient With Hyperphosphatemic Familial Tumoral Calcinosis: Case Report - Rana A. Nabalawi (Case Reports in Medicine)
Hyperphosphatemic familial tumoral calcinosis (HFTC) is a rare hereditary disorder characterized by defective phosphate homeostasis, leading to ectopic calcium deposition in soft tissues. This case report describes a 41 year-old Jordanian male with HFTC and stage 5 chronic kidney disease (CKD) secondary to nonsteroidal anti-inflammatory drug (NSAID) abuse, who presented with symptoms suggestive of uremic pericarditis (UP). His medical history included multiple excisions for tumoral calcinosis, epilepsy, and hypertension. Upon presentation, the patient exhibited severe retrosternal pain, dyspnea, and signs of renal failure. Laboratory findings confirmed severe anemia, metabolic acidosis, hyperkalemia, hyperphosphatemia, and hypocalcemia. Imaging revealed mild pericardial effusion and echogenic kidneys. Following a diagnosis of UP, the patient was initiated on daily hemodialysis and received blood transfusions and antibiotic therapy. His condition improved significantly, with complete regression of pleural effusion and stabilization of renal function. This case emphasizes the importance of effective pain management in HFTC to prevent the misuse of analgesics like NSAIDs, which can lead to severe complications such as UP. This report serves as a valuable reminder of the intricate relationship between medication management and the worsening of underlying health conditions in patients with HFTC.